Rút gọn
a,A=\(\frac{7^{20}-5.7^{19}+4.7^{18}}{7^{20}-7^{19}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có: \(A=\frac {19^{20}+5}{19^{20}-8}=\frac {19^{20}-8+13}{19^{20}-8}=1+\frac {13}{19^{20}-8}\)
\(B=\frac {19^{20}+6}{19^{20}-7}=\frac {19^{20}-7+13}{19^{20}-7}=1+\frac {13}{19^{20}-7}\)
Vì \(19^{20}-8<19^{20}-7\) nên \(\frac {13}{19^{20}-8}>\frac {13}{19^{20}-7}\)
\(\Rightarrow\)\(1+\frac{13}{19^{20}-8}>1+\frac{13}{19^{20}-7}\) Hay \(A>B\)
Vậy A>B
ta có A = \(\frac{19^{20}+5}{19^{20}-8}=\frac{19^{20}-8+13}{19^{20}-8}=1+\frac{13}{19^{20}-8}\)
và B = \(\frac{19^{20}+6}{19^{20}-7}=\frac{19^{20}-7+13}{19^{20}-7}=1+\frac{13}{19^{20}-7}\)
vì \(\frac{13}{19^{20}-8}>\frac{13}{19^{20}-7}\)\(\Rightarrow1+\frac{13}{19^{20}-8}>1+\frac{13}{19^{20}-7}\)\(\Rightarrow A>B\)
\(A=\frac{7^{18}.\left(7^2-5.7+4\right)}{7^{19}.\left(7-1\right)}=\frac{5}{21}\)